REFORMASI BIROKRASI DALAM PERSPEKTIF PERILAKU ADMINISTRASI - Riyadi Riyadi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2008)
Bureaucratic reform has become a part of the entire national reform which covers the aspects of politic, social, economy, and law. Bureaucracy is formed to provide non-discriminatory services to citizens; thus, for this, it needs competent and professional human resource. Demand for bureaucratic reform emerges due to two different perspectives on public administration or bureaucracy. The two perspectives comprise internal and external factors. Internal factors constitutethe defective existing conditions of bureaucracy, such as feudalism, patrimonialism, hedonism, ineffeciency, low competency and so forth.External factors comprising rapid changes and globalization all over the world call for bureaucracy to strengthen its self on all aspects. Bureaucratic reform can be conducted through the restructuring and reorganization of personnel-related government institutions (Ministry of Apparatus Empowerment, National Agency for Public Administration, and National Civil Service Agency). For this purpose, efforts should be made to formulate another concept or model for reorganizing and restructuring bureaucracy as well as for restoring the image of bureaucracy. The newly formed model is expected to be a centralistic system, in which the authority of civil service management is centralized on an independent body. This system differs from centralized government. It is only centralistic within the organization.